Stockholm Norvik Hamn - Vilka navigatoriska risker finns det intill hamnen och dess farled? - Boog, Alexander; Landquist, Johan (My University, 2014)
Stockholm Norvik is a new port which is planned to be built on Norviksudden of Nynäshamn. With the construction of a new port it will affect traffic conditions in its vicinity and it is therefore important to investigate any navigational risks that may arise. This study has focused on four different issues that have starting points in geographic risks, placement of buoys in the area, the junction at Finnhällorna and the traffic flow. The study has been designed in the form of a case study where the primary data collection consists of qualitative semi-structured interviews. There has been much emphasis on the informants' navigational expertise and local knowledge which has limited the choice of informants. The geographical risks the informant’s addresses are mainly cruise traffic and its tender activities affecting traffic in the area as well as the current location of the anchorage. The informants agreed that placement of buoys must be reviewed in the area and reinforced in some places. That also includes speed limits, but the scope and level of restriction was uncertain. The crossing occurring outside Finnhällorna is seen as no major navigational risk since the traffic flow to the port will not achieve a greater quantity and the approach is less complicated when compared to other international ports.
Keywords: Transport; Annan teknik; Transport; Other Engineering and Technologies